Current knowledge among pediatric dentistry specialists in Japan regarding prevention of infective endocarditis. Issue 2 (August 2018) - Kokomoto, Kazuma; Nomura, Ryota; Ohara, Takahiro; Nakatani, Satoshi; Ooshima, Takashi; Nakano, Kazuhiko
Abstract: Infective endocarditis (IE) is a life-threatening disease, with dental procedures known to produce bacteremia considered to be major factors in its development. Thus, prevention of IE onset with antibiotics given prior to performing dental treatments is widely recommended. However, few studies have been conducted to determine the general knowledge of pediatric dentists regarding IE prevention. Members of the Japanese Society of Pediatric Dentistry were invited to participate in a survey in order to elucidate common knowledge among pediatric dentists for prevention of IE. A total of 118 answered the questionnaire, most of whom had experience with prescribing antibiotics for IE prevention. Approximately 80% of those answered that they administer antibiotics only to patients at high risk for IE, though they also noted difficulties understanding which heart diseases are defined as high risk for the disease. As for dental procedures associated with an increased risk for IE, most of the respondents answered dental treatments conducted as surgical procedures, while less invasive procedures were thought to be low risk for IE. More than 80% of the queried pediatric dentists selected oral amoxicillin at a dose of 50 mg/kg of body weight for child patients. Among those, over 50% prescribed antibiotics only prior to performing dental treatment. We found that pediatric dentists in Japan tend to prescribe antibiotics in accordance with the guidelines, though they expressed difficulty with understanding which heart diseases are at high risk of IE, likely due to lack of training in cardiology.